New Approaches for Prediction of Flow Regime Boundaries and Overall Gas Holdups in a Bubble Column Operated with Aqueous Solutions of 2-Pentanol - Stoyan Nedeltchev; Sara Marchini; Markus Schubert; Uwe Hampel (Journal of Chemical Engineering of Japan)
The article reports a new approach for flow regime (FR) identification and a modified correlation for gas holdup prediction in a bubble column (BC) (0.1 m inner diameter) operated with aqueous solutions of 2-pentanol at ambient conditions. The hydrodynamic behavior of mixtures of deionized water (DW) and 2-pentanol with different volume concentrations (0.5 − 2.0 vol.%) was examined. A new algorithm for estimation of the information amount (IA) from a gauge pressure (GP) signal is proposed. It is based on simultaneous statistical and error analyses of the sub-divided GP time series. The new approach extracts detailed hidden information from every sector of the time-dependent GP signal. In case of 0.5 vol.% 2-pentanol dissolved in DW, by means of the local well-pronounced IA minima, three transition velocities Utrans (at 0.043, 0.054 and 0.073 m/s) were reliably identified. The first critical velocity was comparable with the prediction of a well-known empirical correlation. When the volume concentration of 2-pentanol in DW was doubled, then the three Utrans values were distinguished at 0.049, 0.063 and 0.074 m/s, respectively. In addition, the end of the gas maldistribution state was identified at 0.041 m/s. It was found that the increase of the alcohol concentration affects the first and second Utrans values but not the third one, i.e. the onset of the complete foaming state. The overall gas holdups were also successfully predicted in both homogeneous and transition flow regimes of BC operation. One of the parameters (taking part in a dimensionless group about the scale effect) in an existing empirical correlation was modified in order to predict the overall gas holdups recorded in different aqueous solutions of 2-pentanol. The modified parameter was fitted for every mixture investigated. The average relative error was reasonably low in every case.